In silico analyses of essential interactions of iminosugars with the Hex A active site and evaluation of their pharmacological chaperone effects for Tay–Sachs disease. Issue 44 (29th September 2017) - Kato, Atsushi; Nakagome, Izumi; Nakagawa, Shinpei; Kinami, Kyoko; Adachi, Isao; Jenkinson, Sarah F.; Désiré, Jérôme; Blériot, Yves; Nash, Robert J.; Fleet, George W. J.; Hirono, Shuichi
Abstract : DMDP amide restored Hex A activity in the G269S Tay–Sachs patient cells up to 43% of the wild type. Abstract : The affinity of a series of iminosugar-based inhibitors exhibiting various ring sizes toward Hex A and their essential interactions with the enzyme active site were investigated. All the Hex A-inhibiting iminosugars tested formed hydrogen bonds with Arg178, Asp322, Tyr421 and Glu462 and had the favorable cation–π interaction with Trp460. Among them, DMDP amide (6 ) proved to be the most potent competitive inhibitor with a K i value of 0.041 μM. We analyzed the dynamic properties of both DMDP amide (6 ) and DNJNAc (1 ) in aqueous solution using molecular dynamics (MD) calculations; the distance of the interaction between Asp322 and 3-OH and Glu323 and 6-OH was important for stable interactions with Hex A, reducing fluctuations in the plasticity of the active site. DMDP amide (6 ) dose-dependently increased intracellular Hex A activity in the G269S mutant cells and restored Hex A activity up to approximately 43% of the wild type level; this effect clearly exceeded the border line treatment for Tay–Sachs disease, which is regarded as 10–15% of the wild type level. This is a significantly greater effect than that of pyrimethamine, which is currently in Phase 2 clinical trials. DMDP amide (6 ), therefore, represents a new promising pharmacological chaperone candidate for the treatment of Tay–Sachs disease.